Emergency surgery course (ESC®) manual : the official ESTES/AAST guide - Fingerhut, Abe; Leppäniemi, Ari; Coimbra, Raul; Peitzman, Andrew B.; Scalea, Thomas; Voiglio, Eric J. (Springer, 2016)
This manual explains how to make the right decisions on the timing and selection of investigations and surgical procedures in emergency and urgent surgical settings and describes the most widely used procedures step by step with the aid of high-quality illustrations. The goal is to address the situations that can arise in almost any emergency department throughout the world, enabling the surgeon on call to acquire or sharpen the knowledge and skills needed to deal with acute surgical problems in the most appropriate way. The reader will gain a sound understanding of the most efficient diagnostic modalities, pre-, intra-, and postoperative decision-making, and surgical techniques and issues in particular circumstances. The manual stems from an initiative by members of the European Society of Trauma and Emergency Surgery (ESTES) and the American Association for the Surgery of Trauma (AAST) to set up and formalize Emergency Surgery Courses to provide specific training in emergency and acute care surgery. It represents a didactic accompaniment to the course that will guide the beginner and maintain a certain degree of standardization among the more experienced.